2009
DOI: 10.1016/j.jvs.2008.09.070
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopically directed external support of femoral vein valves

Abstract: External valve support by the Vedensky Spiral is an effective and simple method of correction of incompetent femoral vein valves in limbs with primary deep venous reflux. The technical success of the intervention depends on the type of valve insufficiency and the correct choice of spiral diameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…Long-term ulcer healing has been reported in about 50% of patients with one valve repair, and improved long-term results have been reported with multiple reconstructions. [378][379][380][381] External valvuloplasty results vary by technique, with the advocates of the "commissural repair" reporting a competency rate of w60% and freedom from ulcer recurrence rate of w70% at 3 years. 382 Others have reported lower competency (down to 32%) and ulcer-free rates (down to 50%) at 2 years.…”
Section: Level Of Evidence -C]mentioning
confidence: 99%
“…Long-term ulcer healing has been reported in about 50% of patients with one valve repair, and improved long-term results have been reported with multiple reconstructions. [378][379][380][381] External valvuloplasty results vary by technique, with the advocates of the "commissural repair" reporting a competency rate of w60% and freedom from ulcer recurrence rate of w70% at 3 years. 382 Others have reported lower competency (down to 32%) and ulcer-free rates (down to 50%) at 2 years.…”
Section: Level Of Evidence -C]mentioning
confidence: 99%
“…determined competency in 91.6% of femoral vein valves administered endoscopic external support. 9 However, although they stated that symptom severity decreased in their patients, they did not demonstrate this objectively. Wang et al.…”
Section: Discussionmentioning
confidence: 88%
“…In the study of Saraç et al, symptomatic improvement was detected in 51 patients (61.4%) in the 2-year results of surgical external valvuloplasty (EVP) on 83 patients with isolated saphenous vein insufficiency, but no improvement was observed in the remaining 32 patients and additional procedures were performed (7). Makhatilov and et al found that 91.6% of the valves were competent in the femoral veins where they endoscopically applied external support (8). However, they also said that the severity of symptoms decreased in their patients, although they did not objectively show this.…”
Section: Discussionmentioning
confidence: 95%